Global framework against the terrorist diaspora: collateral damages for individuals and states - Sánchez-Frías, Alejandro (My University, 2018)
The so-called “terrorist diaspora” of FTF to their countries of residence after the defeat of Daesh is a primary concern not only for European countries, but also for the international community as a whole. Some studies have been focused on the causes of this phenomenon and its effects. However, less attention has been paid to the effects of counter-terrorism measures. Since Resolution 1373, the United Nations Security Council has been developing a binding global framework against terrorism, and Resolution 2178 is the icing on this cake. This framework, accepted by many regional organizations such as the European Union or the Council of Europe, forces States to adopt measures against FTF in areas of criminal, administrative and civil law. Firstly, these measures affect individuals because of the restrictions imposed on certain fundamental rights, such as privacy or freedom of movement. Secondly, a radical interpretation of these measures followed by its unilateral adoption can cause anarchy in the international relations between the States of origin of FTF and the States of destination. For instance, measures preventing the movement of terrorists can be translated into the expulsion of residents or nationality deprivation, driving them to countries with less capabilities to deal with this risk. A strategy which, at the end, will increase instability in a globalised world. For these reasons, the global framework against FTF should be used as a tool to coordinate efforts, and not as a justification to defend short-term national security interests to the detriment of long-term international security.
Keywords: Terrorismo; Derechos humanos; Nacionalidad; Soberanía